Winners and losers [videorecording] - Dormer, Mike; Fairley, John; Hughes, Gruyneth; Marshall, Jill; Welfare, Simon (Red empire presented by Robert Conquest ; series producer, Gruyneth Hughes, 1990)
War with Germany leads to civil war in Russia Tsar and his family are among the first casualties. Lenin is nearly assassinated while the two central group, the Reds and the Whites fight for control of the empire. Those who suffer most are the people, victims of battle and famine. The Communist Party under Lenin and Trotsky, gain control. When Lenin dies in 1924, the future of the Party is in doubt, except for a revolutionary on the rise ... Joseph Stalin.